Aluminum easy-open lid coiled material outer coating for acid-resistant sterilization process
By using high molecular weight epoxy resin and nano-scale graphene materials in aluminum easy-to-pull coil outer coating, the problem that existing coatings cannot resist acidic corrosion during high-temperature sterilization and cooking is solved, and higher flexibility, corrosion resistance and acid resistance are achieved.
Patent Information
- Application Number
- CN202411939964.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing aluminum easy-to-pull coil outer coating cannot effectively resist acidic erosion during high temperature sterilization and cooking, resulting in whitening, water spots and coating peeling.
The aluminum easy-to-pull coil outer coating consisting of epoxy resin, phenolic resin and nano-scale graphene materials is used to significantly improve the flexibility and corrosion resistance of the coating by combining high molecular weight epoxy resin and nano-graphene.
The coating exhibits excellent acid corrosion resistance under high temperature cooking conditions, ensuring the stability and performance of the aluminum easy-to-pull coil in the sterilization process.
Smart Images

Figure BDA0005212375080000041 
Figure BDA0005212375080000051 
Figure BDA0005212375080000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to an outer coating of an aluminum easy-open lid coil for an acid-resistant sterilization process. Background Art
[0002] Easy-open lids, also known as easy-open lids, are lids with pull rings used to seal cans and beverage cans. They are metal packaging products. They are mostly made of aluminum or tinplate and come in a variety of sizes, suitable for iron cans, aluminum cans, composite cans, PET plastic cans, and paper cans. The production process requires punching and forming by a punching die. Usually, before the aluminum easy-open lid is formed, a coating is applied to the front and back of the aluminum coil to protect the aluminum.
[0003] Coil coatings mainly include 1) epoxy resin type, 2) polyester resin type, and 3) acrylic resin type. Among them, epoxy resin type coatings have the best water resistance, alkali resistance, and chemical resistance. In the manufacturing process of aluminum pull-open lids, the outer coating of the coil is covered on the front of the aluminum coil, which is the top of the pull-open lid. Usually, canned foods such as beverage cans and food cans need to be sterilized and boiled at high temperature after filling food or beverages. In the special boiling and sterilization process, acidic substances such as citric acid and malic acid are added to prevent the bottom of the beverage can from turning black. In this way, the outer coating of the coil on the top of the aluminum pull-open lid will face acid corrosion during high-temperature sterilization and boiling.
[0004] At present, most of the outer coatings for the top of the easy-open lid on the market are made of epoxy resin coatings. Due to the different curing agent materials used in the cross-linking and curing, the film-forming materials are: epoxy-amino resin curing film, epoxy-isocyanate curing film, and epoxy-phenolic resin curing film. The characteristics of the first two curing film-forming coatings make them unable to resist the acid corrosion during high-temperature sterilization and cooking, which causes the top of the aluminum easy-open lid to turn white and produce water spots. In severe cases, the coating will fall off. When epoxy-phenolic coatings use solid epoxy resins sold on the market, their number average molecular weight is low, and their machinability and flexibility are poor. To ensure good water resistance, alkali resistance, and chemical resistance, a higher cross-linking density is required. Once the cross-linking density is increased, there will be contradictions such as poor flexibility and machinability. Summary of the invention
[0005] The present invention proposes an outer coating for an aluminum easy-open lid coil for an acid-resistant sterilization process. The coating forms a protective coating on the surface of the aluminum coil. While having excellent mechanical properties, flexibility, and machinability, it can also meet the requirements of high-temperature sterilization and boiling resistance, especially in the sterilization and boiling process with the addition of acidic substances, and has excellent acid corrosion resistance.
[0006] In order to achieve the above-mentioned purpose, the present invention proposes an outer coating for an aluminum easy-open lid coil for an acid-resistant sterilization process, which includes the following raw materials in percentage by weight: 20% to 40% epoxy resin, 4% to 15% phenolic resin, 1% to 5% blocked isocyanate, 50% to 70% solvent, 0.2% to 3.0% wax powder, 0.01% to 0.5% catalyst, 0.05% to 1.0% defoamer, 0.5% to 2.0% adhesion promoter, 2% to 8% graphene dispersion, and 0.01% to 0.5% leveling agent; wherein the epoxy equivalent of the epoxy resin is 5500 to 6000 g / Eq, and the number average molecular weight is 13500 to 18000.
[0007] According to the present invention, an outer coating for an aluminum easy-open lid coil for an acid-resistant sterilization process is mainly composed of epoxy resin-phenolic resin and isocyanate resin, and a high molecular weight epoxy resin is matched with a nano-scale graphene material. It is used as the outer coating for the coil, which can significantly improve the flexibility and corrosion resistance of the coating system; the coating has excellent leveling performance, a flat surface, hardness, glossiness, solvent wiping resistance, mechanical processing performance, adhesion, and scratch resistance after curing, and has high temperature cooking resistance, especially acid cooking resistance, which can meet the high temperature cooking sterilization process with the addition of acidic substances.
[0008] Optionally, the epoxy resin is prepared by polymerization of the following raw materials through addition polymerization: 60% to 70% of E-51 epoxy resin, 30% to 40% of bisphenol A, and 0.1% to 2.0% of dialkanol tert-butylamine.
[0009] Furthermore, the addition polymerization reaction is as follows: adding the E-51 epoxy resin and the bisphenol A into a reaction container, heating to 110-120° C. while stirring, and maintaining the temperature for 30 minutes, so that the bisphenol A is completely dissolved until the material becomes clear and transparent; after adding the dialkyl tert-butylamine catalyst, heating to 170° C., stirring at 100 rpm for reaction for 30 minutes, during which the material reaction releases heat and the temperature continues to rise to 195-220° C., and then maintaining the temperature at 195-220° C. for 2 hours; then pouring the material from the reaction container and transferring it to a cooling plate, and then crushing it after cooling.
[0010] Optionally, the graphene dispersion is prepared by mixing the following raw materials through high-speed grinding: 15% to 30% graphene, 15% to 30% epoxy resin, 15% to 30% propylene glycol butyl ether and 15% to 30% propylene glycol methyl ether acetate.
[0011] Optionally, the phenolic resin is one or more of mixed cresol-formaldehyde resin, p-tert-butylphenol-formaldehyde resin, bisphenol A-formaldehyde resin, and phenol-formaldehyde resin.
[0012] Optionally, the blocked isocyanate is one or more of hexamethylene diisocyanate, isophorone diisocyanate, meta-xylylene diisocyanate, and toluene diisocyanate.
[0013] Optionally, the solvent is one or more of n-butanol, propylene glycol butyl ether, propylene glycol methyl ether acetate, 100# solvent oil, 150# solvent oil, dibasic acid ester DBE, isophorone, methyl isobutyl ketone, and dipropylene glycol methyl ether.
[0014] Optionally, the wax powder is one or more of polyethylene wax, oxidized polyethylene wax, carnauba wax, Fischer-Tropsch wax, and polytetrafluoroethylene-modified polyethylene wax.
[0015] Optionally, the catalyst is one or more of p-toluenesulfonic acid, dinonylbenzenesulfonic acid, dinonylnaphthalenesulfonic acid, phosphoric acid, and dodecylbenzenesulfonic acid.
[0016] Optionally, the defoaming agent is one or more of a high-carbon alcohol fatty acid ester complex, polyoxyethylene polyoxypropylene pentaerythritol ether, polyoxyethylene polyoxypropanolamine ether, polyoxypropylene oxyethylene glycerol ether, and polydimethylsiloxane.
[0017] Optionally, the adhesion promoter is one or more of epoxy phosphate, polysiloxane, polyester alkylamine salts, and titanate.
[0018] Optionally, the leveling agent is at least one of an organic silicon leveling agent, an acrylic leveling agent and a fluorocarbon leveling agent.
[0019] Optionally, the particle size D50 of the graphene dispersion is 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm.
[0020] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.
[0022] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.
[0023] The test materials used in the present invention are all common commercial products and can be purchased in the market.
[0024] Among them, the epoxy resin is a homemade product, preferably an epoxy resin with an epoxy equivalent of 5500-6000 g / Eq and a number average molecular weight of 13500-18000; in addition, the Nan Ya NPES-907 in the following comparative example is an epoxy resin with an epoxy equivalent of 1500-1800 g / Eq.
[0025] Among them, the phenolic resin is used as a crosslinking agent, and is selected from available mixed cresol-formaldehyde resin, p-tert-butylphenol-formaldehyde resin, bisphenol A-formaldehyde resin, phenol-formaldehyde resin, preferably bisphenol A-formaldehyde resin, and the commercially available allnex resin PHENODUR PR 515 is selected. In addition, allnex CYMEL U-227-8 in the following comparative examples is a urea-formaldehyde resin crosslinking agent.
[0026] Among them, the blocked isocyanate is used as a cross-linking agent and is selected from one or more of the available hexamethylene diisocyanate, isophorone diisocyanate, meta-xylylene diisocyanate, and toluene diisocyanate, preferably blocked isophorone diisocyanate, and Covestro Desmodur BL 2078 / 2 can be selected.
[0027] The solvent includes one or more of n-butanol, propylene glycol butyl ether, propylene glycol methyl ether acetate, 100# solvent oil, 150# solvent oil, dibasic acid ester DBE, isophorone, methyl isobutyl ketone, and dipropylene glycol methyl ether. N-butanol, propylene glycol butyl ether, propylene glycol methyl ether acetate, 150# solvent oil, and dibasic acid ester DBE are preferred.
[0028] The wax powder is at least one of polyethylene wax, oxidized polyethylene wax, carnauba wax, Fischer-Tropsch wax and polytetrafluoroethylene modified polyethylene wax, preferably polytetrafluoroethylene modified polyethylene wax, and commercially available Clariant Ceridust 9322F can be selected.
[0029] The catalyst is one or more of blocked p-toluenesulfonic acid, dinonylbenzenesulfonic acid, dinonylnaphthalenesulfonic acid, phosphoric acid, and dodecylbenzenesulfonic acid, preferably dodecylbenzenesulfonic acid, and the commercially available King's NACURE XC-C203 can be selected.
[0030] The defoaming agent is one or more of a high-carbon alcohol fatty acid ester complex, polyoxyethylene polyoxypropylene pentaerythritol ether, polyoxyethylene polyoxypropanolamine ether, polyoxypropylene oxyethylene glycerol ether, and polydimethylsiloxane, preferably polydimethylsiloxane, and commercially available BASF FoamStar SI 2210 is selected.
[0031] The adhesion promoter is one or more of epoxy phosphate, polysiloxane, polyester alkylamine salts, and titanate, preferably titanate, and commercially available Shuguang Chemical SG-Ti 595 can be selected.
[0032] The leveling agent is at least one of an organic silicon leveling agent, an acrylic leveling agent, and a fluorocarbon leveling agent, preferably an organic silicon leveling agent, and the commercially available BYK-307 can be selected.
[0033] The particle size D50 of the graphene dispersion is 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, preferably 3 μm.
[0034] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0035] Example
[0036] An external coating for an aluminum easy-open lid coil for acid-resistant sterilization process comprises the following raw material components by weight percentage:
[0037] Table 1
[0038]
[0039]
[0040] Specifically, the preparation of epoxy resin a comprises the following steps:
[0041] (1) Add 316.28g E-51 epoxy resin and 182.97g bisphenol A into a 1L separable four-necked flask, heat to 110-120°C while stirring, and keep the temperature constant for 30 minutes to completely dissolve the bisphenol A until the material is clear and transparent. Then, add 7.5g dialkylol tert-butylamine catalyst and heat to 170°C, stir at 100rpm and react for 30 minutes. During this period, the material will continue to heat up to 195-200°C due to the heat release, and then keep the temperature constant at 195-200°C for 2 hours.
[0042] (2) The material in the flask was poured out and transferred to a cooling plate, and then pulverized after cooling to obtain a self-made epoxy resin a with an epoxy equivalent of 5500 to 6000 g / Eq and a number average molecular weight of 13500 to 18000.
[0043] The preparation of epoxy resin b comprises the following steps:
[0044] (1) Add 315.65g E-51 epoxy resin and 184.35g bisphenol A into a 1L separable four-necked flask, heat to 110-120°C while stirring, and keep the temperature constant for 30 minutes to completely dissolve the bisphenol A until the material is clear and transparent. Then, add 7.5g dialkylol tert-butylamine catalyst and heat to 170°C, stir at 100rpm and react for 30 minutes. During this period, the material will continue to heat up to 200-220°C due to the heat release, and then keep the temperature constant at 200-220°C for 2 hours.
[0045] (2) The material in the flask was poured out and transferred to a cooling plate, and then pulverized after cooling to obtain a self-made epoxy resin b, which has an epoxy equivalent of 8000 to 8500 g / Eq and a number average molecular weight of 20000 to 25500.
[0046] The preparation of epoxy resin c comprises the following steps:
[0047] (1) Add 332.4g E-51 epoxy resin and 167.6g bisphenol A into a 1L separable four-necked flask, heat to 110-120°C while stirring, and keep the temperature constant for 30 minutes to completely dissolve the bisphenol A until the material is clear and transparent. Then, add 5.5g dialkylol tert-butylamine catalyst and heat to 170°C, stir at 100rpm and react for 30 minutes. During this period, the material reaction exothermicity will continue to rise to 195-200°C, and then keep the temperature constant at 195-200°C for 2 hours.
[0048] (2) The material in the flask was poured out and transferred to a cooling plate. After cooling, the material was crushed to obtain a self-made epoxy resin c, which had an epoxy equivalent of 1500 to 1800 g / Eq and a number average molecular weight of 4000 to 6000.
[0049] The preparation of epoxy resin d comprises the following steps:
[0050] (1) Add 322.05g E-51 epoxy resin and 177.95g bisphenol A into a 1L separable four-necked flask, heat to 110-120°C while stirring, and keep the temperature constant for 30 minutes to completely dissolve the bisphenol A until the material is clear and transparent. Then, add 6.5g dialkylol tert-butylamine catalyst and heat to 170°C, stir at 100rpm and react for 30 minutes. During this period, the material reaction exotherm will continue to heat up to 195-200°C, and then keep the temperature constant at 195-200°C for 2 hours.
[0051] (2) The material in the flask was poured out and transferred to a cooling plate. After cooling, the material was crushed to obtain a self-made epoxy resin d, which had an epoxy equivalent of 2800 to 3200 g / Eq and a number average molecular weight of 7500 to 10000.
[0052] The preparation of graphene dispersion comprises the following steps:
[0053] (1) Add 45 g of graphene, 100 g of the above-mentioned epoxy resin a, 120 g of propylene glycol butyl ether, and 120 g of propylene glycol methyl ether acetate into a grinding cylinder and disperse them evenly at a rotation speed of 1000 rpm.
[0054] (2) Add 300 g of zirconium beads with a particle size of 0.5 mm and 300 g of zirconium beads with a particle size of 1 mm, grind at 3500 rpm for 3-4 hours under the condition of passing cooling water, and use a particle size analyzer to measure the particle size D50 of the dispersion to be 0.5-5 μm, thereby obtaining a graphene dispersion.
[0055] The preparation of the outer coating of the aluminum easy-open lid coil for acid-resistant sterilization process includes the following steps:
[0056] (1) Add the crushed homemade epoxy resin, 100# solvent oil, propylene glycol monobutyl ether, and propylene glycol methyl ether acetate into a dispersion tank according to the formula in Table 1 above, disperse at 800 rpm for 2 h until the material is clear and transparent without particles, and cool for use.
[0057] (2) Add the materials n-butanol, 100# solvent oil, propylene glycol butyl ether, dibasic acid ester DBE, 150# solvent oil, phenolic resin, and isocyanate in order and disperse them evenly at 600 rpm for 15 minutes.
[0058] (3) Add catalyst, wax powder, defoamer, adhesion promoter, graphene dispersion and leveling agent in sequence under stirring, disperse at 600 rpm for 30 min until uniform, filter and obtain the outer coating of aluminum easy-open lid coil for acid-resistant sterilization process.
[0059] Test example
[0060] The coatings of the above examples and comparative examples were tested: passivated aluminum, coating thickness: 6 g / m 2 ; Coating method: scraping with a wire rod; Baking conditions: constant temperature of 241-249℃ for 5-10s.
[0061] Test items: gloss, hardness, adhesion, solvent resistance, scratch resistance, boiling resistance, impact resistance, and machinability.
[0062] 1. Coating gloss test: According to GB / T 9754, use a gloss meter to measure the gloss of the coating at a 60° angle.
[0063] 2. Pencil hardness test: According to GB / T 6739, use a Chinese pencil to measure the maximum pencil hardness that does not break the coating.
[0064] 3. Adhesion test: According to GB / T 1720, use a grid knife to cut 6-8 cross grids with an interval of 1mm on the coating, then tear the grid with 3M tape and visually observe the coating film shedding situation. It is divided into 0-5 levels, and the smaller the level, the better the adhesion.
[0065] 4. Resistance to solvent wiping: According to GB / T 23989, the coating surface is wiped back and forth with absorbent cotton soaked in methyl ethyl ketone under a pressure of 1 kg. The larger the value of the complete back and forth wiping process, the better the resistance to solvent wiping.
[0066] 5. Scratch resistance: According to GB / T 9279, use a scratch tester to measure the minimum load value that can penetrate the coating, which is the scratch resistance value of the coating. The larger the value, the better.
[0067] 6. Retort resistance test: According to GB / T 1733, after the coating is prepared, it is sterilized by high-temperature retorting in liquid and steam phases at 127°C for 60 minutes in a high-pressure vertical sterilizer to observe whether the coating has water vapor penetration, whitening, bubbling, paint film shedding and other abnormalities.
[0068] 7. Impact test: According to GB / T 1732, use a 1 kg hammer of the impact tester to drop the test sample from a height of 50 cm, soak it in copper sulfate solution for 2 minutes, and observe whether there is corrosion at the impact site.
[0069] 8. Machinability test: After the coating is made into a plate, the sample is punched out through an unequal angle can-RC box mold and sterilized by high-temperature steaming. The cracking of the paint film at the four corners of the RC box with different arcs is observed. It is divided into 0-4 levels, with 0 indicating the best machinability and flexibility, and 4 being the worst.
[0070] The performance test results of the coatings of the embodiments and comparative examples are shown in Table 2.
[0071] Table 2 Performance test results of the coatings of the embodiments and comparative examples
[0072]
[0073]
[0074] As shown in Table 2, Example 1 and Example 2 can meet the requirements of high temperature steaming sterilization process of 2% citric acid-water solution at 127°C for 60 minutes under the premise of good flexibility and machinability; the epoxy resin equivalent used in Example 2 is too high, and the problem of poor surface leveling of the paint film occurs due to excessive viscosity and exceeding the construction conditions. Among them, Example 3 has a slightly lower number average molecular weight of epoxy resin, resulting in a slight decrease in adhesion, and the resistance to steaming of 2% citric acid-water solution also turns white; Example 4 and Comparative Example 1 are compared with Example 1 and Example 2. The 907 epoxy resin in Comparative Example 1 has the smallest number average molecular weight compared to the resin used in Example 4, and its resistance to steaming of 2% citric acid-water solution is the worst, and the undesirable phenomenon of whitening occurs, which shows that high molecular weight is necessary in the acid-resistant steaming sterilization process. Comparison between Example 1 and Comparative Example 2 shows that the curing agent of Comparative Example 2 uses urea-formaldehyde amino resin. Combined with the test results and the characteristics of the epoxy-amino resin coating system, it is not surprising that the paint film resistant to 2% citric acid loses gloss, turns white, and falls off seriously after sterilization and boiling. Comparison between Example 1 and Comparative Example 3 shows that in epoxy-phenolic coating, adding a certain amount of nano-graphene material can significantly improve the coating's resistance to high-temperature boiling of 2% citric acid-water solution at 127°C for 60 minutes; comparison between Example 5 and Example 7 shows that the addition of too little or too much graphene material in acid-resistant high-temperature boiling sterilization can not achieve the expected effect, and the addition of too much graphene material can also reversely affect the cross-linking density of the paint film and produce surface competition with wax powder, thereby causing the paint film surface to have a slight orange peel, and the gloss, scratch resistance, solvent wiping resistance, and machinability and other properties are reduced.
[0075] In summary, the outer coating of the aluminum easy-open lid coil for acid-resistant sterilization process in the embodiment of the present application has excellent flexibility, machinability and acid-resistant high-temperature boiling resistance while ensuring that other basic properties meet the requirements of use, and can meet the acid-resistant high-temperature boiling sterilization process of the aluminum easy-open lid.
[0076] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily being directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.
[0077] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. An external coating for an aluminum easy-open lid coil for acid-resistant sterilization process, characterized in that: The invention comprises the following raw materials in percentage by weight: 20% to 40% epoxy resin, 4% to 15% phenolic resin, 1% to 5% blocked isocyanate, 50% to 70% solvent, 0.2% to 3.0% wax powder, 0.01% to 0.5% catalyst, 0.05% to 1.0% defoamer, 0.5% to 2.0% adhesion promoter, 2% to 8% graphene dispersion and 0.01% to 0.5% leveling agent; wherein the epoxy equivalent of the epoxy resin is 5500 to 6000 g / Eq and the number average molecular weight is 13500 to 18000.
2. The outer coating of the aluminum easy-open lid coil for acid-resistant sterilization process according to claim 1, characterized in that: The epoxy resin is prepared by polymerization of the following raw materials through addition polymerization: 60% to 70% of E-51 epoxy resin, 30% to 40% of bisphenol A, and 0.1% to 2.0% of dialkanol tert-butylamine.
3. The outer coating of the aluminum easy-open lid coil for acid-resistant sterilization process according to claim 2, characterized in that: The polyaddition reaction is as follows: adding the E-51 epoxy resin and the bisphenol A into a reaction container, heating to 110-120° C. while stirring, and maintaining the temperature for 30 minutes, so that the bisphenol A is completely dissolved until the material becomes clear and transparent; after adding the dialkylol tert-butylamine catalyst, heating to 170° C., stirring at 100 rpm for 30 minutes, during which the material reaction releases heat and the temperature continues to rise to 195-220° C., and then maintaining the temperature at 195-220° C. for 2 hours; then pouring the material from the reaction container and transferring it to a cooling plate, and then crushing it after cooling.
4. The outer coating of the aluminum easy-open lid coil for acid-resistant sterilization process according to claim 1, characterized in that: The graphene dispersion is prepared by mixing the following raw materials through high-speed grinding: 15% to 30% of graphene, 15% to 30% of the epoxy resin, 15% to 30% of propylene glycol butyl ether and 15% to 30% of propylene glycol methyl ether acetate.
5. The outer coating of the aluminum easy-open lid coil for acid-resistant sterilization process according to claim 1, characterized in that: The phenolic resin is one or more of mixed cresol-formaldehyde resin, p-tert-butylphenol-formaldehyde resin, bisphenol A-formaldehyde resin, and phenol-formaldehyde resin.
6. The outer coating of the aluminum easy-open lid coil for acid-resistant sterilization process according to claim 1, characterized in that: The blocked isocyanate is one or more of hexamethylene diisocyanate, isophorone diisocyanate, meta-xylylene diisocyanate and toluene diisocyanate.
7. The outer coating of the aluminum easy-open lid coil for acid-resistant sterilization process according to claim 1, characterized in that: The solvent is one or more of n-butanol, propylene glycol butyl ether, propylene glycol methyl ether acetate, 100# solvent oil, 150# solvent oil, dibasic acid ester DBE, isophorone, methyl isobutyl ketone, and dipropylene glycol methyl ether.
8. The outer coating of the aluminum easy-open lid coil for acid-resistant sterilization process according to claim 1, characterized in that: The wax powder is one or more of polyethylene wax, oxidized polyethylene wax, carnauba wax, Fischer-Tropsch wax, and polytetrafluoroethylene modified polyethylene wax; The catalyst is one or more of p-toluenesulfonic acid, dinonylbenzenesulfonic acid, dinonylnaphthalenesulfonic acid, phosphoric acid and dodecylbenzenesulfonic acid.
9. The outer coating of the aluminum easy-open lid coil for acid-resistant sterilization process according to claim 1, characterized in that: The defoaming agent is one or more of a high-carbon alcohol fatty acid ester complex, polyoxyethylene polyoxypropylene pentaerythritol ether, polyoxyethylene polyoxypropanolamine ether, polyoxypropylene oxyethylene glycerol ether, and polydimethylsiloxane; The adhesion promoter is one or more of epoxy phosphate, polysiloxane, polyester alkylamine salt, and titanate; The leveling agent is at least one of an organic silicon leveling agent, an acrylic leveling agent and a fluorocarbon leveling agent.
10. The outer coating of the aluminum easy-open lid coil for acid-resistant sterilization process according to claim 1, characterized in that: The particle size D50 of the graphene dispersion is 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm.
Citation Information
Patent Citations
Epoxy graphene heavy corrosion-resistant coating, and preparation method and application thereof
CN107739566A
Coiled material coating and preparation method thereof
CN114133833A